2002
DOI: 10.1091/mbc.02-01-0008
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegansInositol 5-Phosphatase Homolog Negatively Regulates Inositol 1,4,5-Triphosphate Signaling in Ovulation

Abstract: Ovulation in Caenorhabditis elegans requires inositol 1,4,5-triphosphate (IP 3 ) signaling activated by the epidermal growth factor (EGF)-receptor homolog LET-23. We generated a deletion mutant of a type I 5-phosphatase, ipp-5, and found a novel ovulation phenotype whereby the spermatheca hyperextends to engulf two oocytes per ovulation cycle. The temporal and spatial expression of IPP-5 is consistent with its proposed inhibition of IP 3 signaling in the adult spermatheca. ipp-5 acts downstream of let-23, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 47 publications
1
96
1
Order By: Relevance
“…Loss of function of lfe-2 (encoding the IP3 kinase) or ipp-5 (encoding type I inositol polyphosphate 5-phosphatase) bypasses the defect in the interaction between the oocyte and the spermatheca (Clandinin et al 1998;Bui and Sternberg 2002). We found that loss of function of ipp-5 and lfe-2 partially rescued the defects in the contraction of the sheath cells and the dilation of the spermatheca in the fli-1 mutants.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Loss of function of lfe-2 (encoding the IP3 kinase) or ipp-5 (encoding type I inositol polyphosphate 5-phosphatase) bypasses the defect in the interaction between the oocyte and the spermatheca (Clandinin et al 1998;Bui and Sternberg 2002). We found that loss of function of ipp-5 and lfe-2 partially rescued the defects in the contraction of the sheath cells and the dilation of the spermatheca in the fli-1 mutants.…”
Section: Resultsmentioning
confidence: 73%
“…The contraction of the sheath cells and dilation of the spermatheca is triggered by LIN-3/LET-23 EGF signaling, which most likely stimulates hydrolysis of PIP2 into IP3 (Bui and Sternberg 2002;Yin et al 2004). In other systems, IP3 has been shown to excite intracellular calcium release channels and cause a transient increase in intracellular calcium (Berridge 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that the myoepithelial sheath pulls dilating spermatheca and facilitates dilation (McCarter et al, 1997). Genetic studies show that spermathecal dilation is mediated by an inositol triphosphate pathway (Clandinin et al, 1998;Bui and Sternberg, 2002), suggesting strongly that calcium is the second messenger. Nonetheless, absence of troponin in the spermatheca suggests that spermathecal dilation is regulated by a different mechanism from sheath contraction.…”
Section: Discussionmentioning
confidence: 99%
“…A subtle sperm defect may thus not affect the overall brood size of the RNAi-treated animal provided excess numbers of oocytes are available for fertilization. Disruption of the C. elegans inositol triphosphate signaling pathway results in ovulation of increased numbers of unfertilized oocytes (50). Interestingly, the archetypal M1 metallopeptidase, aminopeptidase N/CD13, has been shown to elevate intracellular Ca 2ϩ levels in monocytes through signal transduction pathways involving inositol triphosphate and mitogen-activated protein kinases (51).…”
Section: Fig 3 Silencing Pam-1 By Rnai Shows That It Has Roles In Rmentioning
confidence: 99%